Phycobiliproteins—A Family of Algae-Derived Biliproteins: Productions, Characterization and Pharmaceutical Potentials - Chen, Huaxin; Qi, Hongtao; Xiong, Peng (Marine drugs, 2022)
Phycobiliproteins (PBPs) are colored and water-soluble biliproteins found in cyanobacteria, rhodophytes, cryptomonads and cyanelles. They are divided into three main types: allophycocyanin, phycocyanin and phycoerythrin, according to their spectral properties. There are two methods for PBPs preparation. One is the extraction and purification of native PBPs from Cyanobacteria, Cryptophyta and Rhodophyta, and the other way is the production of recombinant PBPs by heterologous hosts. Apart from their function as light-harvesting antenna in photosynthesis, PBPs can be used as food colorants, nutraceuticals and fluorescent probes in immunofluorescence analysis. An increasing number of reports have revealed their pharmaceutical potentials such as antioxidant, anti-tumor, anti-inflammatory and antidiabetic effects. The advances in PBP biogenesis make it feasible to construct novel PBPs with various activities and produce recombinant PBPs by heterologous hosts at low cost. In this review, we present a critical overview on the productions, characterization and pharmaceutical potentials of PBPs, and discuss the key issues and future perspectives on the exploration of these valuable proteins.